Vitamin deficiency prevalence in primary school children in Punjab, India - Batta, Meenal; Gupta, Naveenta; Goyal, Geetika; Jain, Amit (International Journal of Research in Medical Sciences, 2016)
Background: Vitamin deficiencies are the conditions which are prevalent in the society and parents are unaware of them due to their asymptomatic nature. Overcoming this deficiency is integral in achieving the second Sustainable Development Goal charted out by the United Nations. Treatable and preventable nature of these conditions needs to be emphasized. Aims and objectives of the study were to study the prevalence of clinical features of vitamin deficiencies in primary school children. Methods: This single point cross sectional study was conducted in primary school children in Faridkot and comprised of students in the age group of 5-11 years. A total of 849 students were clinically examined. The clinical features of vitamin deficiencies were recorded. Descriptive analysis was used for interpretation. Results: Overall incidence of vitamin deficiency features was 18.96%. The features of vitamin A, B complex, C, and D deficiency were seen in 7.18%, 18.02%, 3.06% and 8.48% respectively. Some children have more than one deficiency features. Conclusions: The primary school children do suffer from vitamin deficiencies and there should be timely evaluation for these diseases. Larger studies substantiated with blood levels would provide more insight into these conditions.